The male and female perspective in the link between male infant care and mating behaviour in Barbary macaques. (8th September 2019) - Kuběnová, Barbora; Ostner, Julia; Schülke, Oliver; Majolo, Bonaventura; Šmilauer, Petr; Waterman, James; Tkaczynski, Patrick; Konečná, Martina
Abstract: Infant care from adult males is unexpected in species with high paternity uncertainty. Still, males of several polygynandrous primates engage in frequent affiliative interactions with infants. Two non‐exclusive hypotheses link male infant care to male mating strategies. The paternal investment hypothesis views infant care as a male strategy to maximize the survival of sired offspring, while the mating effort hypothesis predicts that females reward males who cared for their infant by preferably mating with them. Both hypotheses predict a positive relationship between infant care and matings with a particular female. However, the paternal investment hypothesis predicts that increased matings come before infant care whereas the mating effort hypothesis predicts that infant care precedes an increase in matings. Both hypotheses are usually tested from the perspective of the proportion of matings and care that individual females engage in and receive, rather than from the perspective of the care and mating behaviour of individual males. We tested the relationships between care and mating from both female and male perspectives in Barbary macaques. Mating predicted subsequent care and care predicted subsequent mating when viewed from the male but not the female perspective. Males mainly cared for infants of their main mating partners, but infants were not mainly cared for by their likely father. Males mated more with the mothers of their favourite infants, but females did not mate more with the main caretakers of their infants. We suggest that females do not choose their mating partners based on previous infant care, increasing paternity confusion. Males might try to increase paternal investment by distributing the care according to their own instead of female mating history. Further, males pursue females for mating opportunities based on previous care.